2015
DOI: 10.1136/jclinpath-2014-202658
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment lymphocyte–monocyte ratio as a potential prognostic factor in a cohort of patients with upper tract urothelial carcinoma

Abstract: In the cohort studied, patients with an elevated (≥2) preoperative LMR had a subsequently longer OS after radical surgery for UTUC, compared with those with a low (<2) preoperative LMR. Thus, we believe this parameter might be considered an additional prognostic factor in UTUC in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The association between LMR and OS was reported in 44 studies enrolling 14,984 patients with various cancer types [8, 1013, 1517, 1921, 2327, 2933, 3540, 4246, 48, 49, 51, 53–56, 5862]. Five of the eligible 44 studies (11%) reported a non-statistically significant hazard ratio.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The association between LMR and OS was reported in 44 studies enrolling 14,984 patients with various cancer types [8, 1013, 1517, 1921, 2327, 2933, 3540, 4246, 48, 49, 51, 53–56, 5862]. Five of the eligible 44 studies (11%) reported a non-statistically significant hazard ratio.…”
Section: Resultsmentioning
confidence: 98%
“…Twenty-one studies provided sufficient data for the meta-analysis of the correlation between LMR and clinicopathological characteristics (Table 3) [10, 2224, 2932, 37, 39, 42, 43, 46, 51, 5861]. Urothelial carcinoma, esophageal cancer, gastric cancer, renal cell carcinoma, lung cancer, DLBCL and Hodgkin's lymphoma were investigated in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress, reperfusion damage, and increased reactive oxygen species (ROS) were observed in the lungs of patients with APE. 19 Also, LMR was associated with vascular diseases such as peripheral arterial diseases and coronary artery diseases. 12 Marchena et al observed that increased IL-6 levels were related with mortality in patients with APE.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, regardless of stage, the maintenance and development of the systemic inflammatory responses have been consistently linked to poorer prognosis 24,25. Although many organ systems act in the activation of systemic inflammatory responses, the common measurements of the magnitude of activation are circulating cellular components and acute-phase proteins.…”
Section: Discussionmentioning
confidence: 99%